1997
DOI: 10.1007/s004600050291
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of Lanthanum-carbon clusters

Abstract: As the attachment of a metal change the molecular and electronic structure of carbon clusters, the electronic properties as ionization potentials (IP) and electron affinities (EA) for small Lanthanum-carbon clusters LaC n with n=1-6 have been investigated theoretically. They were studied by density-functional-theory (DFT) within LDA and considering Gradient corrections (GC) for the exchange-correlation potential ( Becke-Perdew). The results for both quantities were obtained in good agreement with the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…For example, in Fig. 1a, it can be seen that the LaC 5 and C 13 cluster existed independently of each other, and coalesced at about 530 ps and that the LaC 19 was formed after the addition of a carbon atom at about 550 ps When the cluster was smaller than LaC 5 , short carbon chains surrounded the La atom (in a fan-type structure [20,21]), as is shown in Fig. 1b.…”
Section: Lanthanum-containing Systemmentioning
confidence: 83%
“…For example, in Fig. 1a, it can be seen that the LaC 5 and C 13 cluster existed independently of each other, and coalesced at about 530 ps and that the LaC 19 was formed after the addition of a carbon atom at about 550 ps When the cluster was smaller than LaC 5 , short carbon chains surrounded the La atom (in a fan-type structure [20,21]), as is shown in Fig. 1b.…”
Section: Lanthanum-containing Systemmentioning
confidence: 83%
“…The group IIIa carbides with more than two carbon atoms were studied theoretically before, and it was found that MC 3 (MϭY,La) carbides ex-hibit ring equilibrium structures. 17,19,35,36 A ring equilibrium geometry was also predicted for the ground state of the ScC 3 molecule. 12 Several geometrical arrangements for ScC 3 are considered here at the DFT level; these included C 2v ring, C ϱv linear, C 2v top, C s bend, and nonplanar C 3v structures ͑Fig.…”
Section: à In Ground and Electronic Excited Statesmentioning
confidence: 95%
“…11 The C 2v ring structure for ScC 3 is also reasonable since the isoelectronic YC 3 and LaC 3 clusters are known to have the same structure from previous theoretical studies. [14][15][16][17][18] The trend of the EA shown in Fig. 3 is interesting.…”
Section: Preliminary Theoretical Calculationsmentioning
confidence: 99%
“…13 Other MC 3 clusters studied theoretically involve YC 3 and LaC 3 , both of which have been concluded to have C 2v ring structures. [14][15][16][17][18] In the present paper, we report vibrationally resolved PES spectra of MC 3…”
Section: Introductionmentioning
confidence: 99%